The GBA p.Trp378Gly mutation is a probable French‐Canadian founder mutation causing Gaucher disease and synucleinopathies. Issue 3 (16th July 2018) - Ruskey, J.A.; Zhou, S.; Santiago, R.; Franche, L.‐A.; Alam, A.; Roncière, L.; Spiegelman, D.; Fon, E.A.; Trempe, J.‐F.; Kalia, L.V.; Postuma, R.B.; Dupre, N.; et al.
Abstract : Biallelic GBA mutations cause Gaucher disease (GD), and heterozygous carriers are at risk for synucleinopathies. No founder GBA mutations in French‐Canadians are known. GBA was fully sequenced using targeted next generation and Sanger sequencing in French‐Canadian Parkinson disease (PD) patients ( n  = 436), rapid eye movement (REM)‐sleep behavior disorder (RBD) patients ( n  = 189) and controls ( n  = 891). Haplotype, identity‐by‐descent (IBD) and principal component analyses (PCA) were performed using single nucleotide polymorphism‐chip data. Data on GD patients from Toronto and Montreal were collected from patients' files. A GBA p.Trp378Gly mutation was identified in two RBD and four PD patients (1% of all patients combined), and not in controls. The two RBD patients had converted to DLB within 3 years of their diagnosis. Haplotype, IBD and PCA analysis demonstrated that this mutation is from a single founder. Out of 167 GD patients screened, 15 (9.0%) carried the p.Trp378Gly mutation, all in trans with p.Asn370Ser. Three (20%) of the GD patients with the p.Trp378Gly mutation had developed Parkinsonism, and 11 patients had family history of PD. The p.Trp378Gly mutation is the first French‐Canadian founder GBA mutation to be described, which leads to synucleinopathies and to GD type 1 when in compound heterozygosity with p.Asn370Ser. Abstract : A French‐Canadian founder mutation in GBA, p.Trp378Gly, is located between the enzyme active site and the binding area of Saposin C. This mutation causes Gaucher disease in compound heterozygous carriers, with or without Parkinson disease, and is a risk factor for synucleinopathies in heterozygous carriers.